Impact of using Islamic microfinance products on Mauritanian microentrepreneurs’ income evidence from PROCAPEC- Nouakchot - Maouloud, Vatimetou Mokhtar; Othman, Anwar Hasan Abdullah (İLKE İlim Kültür Eğitim Vakfı, 2021)
This study examines the impact of using Islamic microfinance products on the Mauritanian microentrepreneurs’ income level. The study is purely quantitative, and it uses cross-sectional design data, which was gathered through a questionnaire from a sample of 381 beneficiaries of an Islamic microfinance institution (PROCAPEC). It uses Structural Equation Modeling (SEM) to determine the effectiveness of using Islamic microfinance products on the beneficiaries’ income as well as to test the moderator effect of gender on the relationship in the model. The research found out that the use of Islamic microfinance products has increased the beneficiaries’ income; however, gender has no moderator effect on the relationship between the usage of Islamic microfinance products and income level. These findings help the policymakers and managers of Islamic microfinance consider the factors increasing Islamic microfinance products’ usage to reduce poverty in the country. This study is among the pioneer in the field of Islamic microfinance in Mauritania due to the scarcity of studies in the geographical context.